A43 LONG-TERM EFFICACY AND SAFETY OF OBETICHOCLIC ACID IN PRIMARY BILIARY CHOLANGITIS: RESPONDER ANALYSIS OF OVER 5 YEARS OF TREATMENT IN THE POISE TRIAL. (4th March 2021) - Hirschfield, G; Jones, D; Carbone, M; Bowlus, C L; Nevens, F; Kremer, A E; Liberman, A; MacConell, L; Hansen, B E
Abstract: Background: Obeticholic acid (OCA), a potent farnesoid X receptor agonist, is approved as second-line treatment for primary biliary cholangitis (PBC) in patients with an incomplete response or intolerance to ursodeoxycholic acid. Aims: We evaluated the effect of OCA in PBC patients enrolled in the POISE trial, comparing those who did or did not achieve the POISE response criteria. Methods: The phase 3, randomized, double-blind, 1-year POISE trial evaluated the efficacy and safety of OCA 5 and 10 mg vs placebo in patients with PBC; a 5-year open-label extension followed in which all patients received OCA. This analysis evaluated longer-term efficacy and safety in patients who achieved the POISE primary endpoint of alkaline phosphatase (ALP) <1.67 × upper limit of normal (ULN), total bilirubin <ULN, and ALP decrease >15% from baseline after 1 year of OCA and in patients who were incomplete responders. Results: The analysis included 86 patients who achieved the POISE primary endpoint at year 1 of OCA treatment and 107 incomplete responders (mean baseline ALP, 268 vs 356 U/L, respectively; P <0.0001). Mean change from baseline in ALP at year 5 was –101 U/L for responders and –121 U/L for incomplete responders ( P <0.0001; Figure ). Median (Q1, Q3) baseline GLOBE 10-year risk of event scores were 16 (11, 23) for responders and 25 (15, 43) for incomplete responders. Change from baseline in median (Q1, Q3) GLOBE 10-year risk of event at year 1, which includes age and thus increases with time, was –2 (–4, 2) for responders and –2 (–6, 4) for incomplete responders; at year 5, these changes were 2 (–2, 7) and 4 (–4, 11), respectively. Median (Q1, Q3) baseline UK-PBC 10-year risk of event scores were 5 (3, 8) for responders and 8 (4, 16) for incomplete responders. Change from baseline in median (Q1, Q3) UK-PBC 10-year risk of event at year 1 was –1 (–3, 0.2) for responders and –1 (–3, 1) for incomplete responders; at year 5, these changes were –0.8 (–2, 0.2) and –0.05 (–2, 2), respectively. The most frequently reported AEs among responders and incomplete responders were pruritus (67%, 86%) and fatigue (35%, 31%). Conclusions: OCA treatment improved key biochemical markers of PBC, regardless of achieving the POISE primary endpoint after 1 year of OCA treatment. Changes in biochemical parameters over time were often similar between groups. Funding Agencies: Intercept Pharmaceuticals